The Association Between the Use of Oclacitinib and Antibacterial Therapy in Dogs With Allergic Dermatitis: A Retrospective Case-Control Study - Rynhoud, Hester; Gibson, Justine S.; Meler, Erika; Soares Magalhães, Ricardo J. (Frontiers in Veterinary Science, 2021)
Background – Canine allergic dermatitis, including atopic dermatitis, often requires antibacterial therapy for concurrent infections. Oclacitinib is indicated for treatment of pruritus associated with allergic dermatitis and the clinical manifestations of atopic dermatitis in dogs aged ≥12 months. Hypothesis/Objectives – We aimed to determine if there was a quantitative difference in antibacterial use by dogs with allergic dermatitis receiving oclacitinib vs. other anti-pruritic therapies and before vs. after oclacitinib. Animals – In this retrospective case-control study, cases (n = 58) included dogs suffering from allergic dermatitis aged ≥12 months receiving oclacitinib and controls (n = 205) were counterpart dogs treated with other anti-pruritic therapies. Methods – Clinical histories of dogs with allergic dermatitis were collected from a small animal university hospital. Multivariable logistic regression models were developed adjusting for underlying skin or ear conditions to determine whether cases were prescribed fewer antibacterials than controls. Results – The odds of systemic antibacterial usage were lower in cases vs. controls (odds ratio [OR]: 0.29 [95% confidence interval 0.12-0.71]; P = 0.007). The odds of amoxycillin clavulanic acid usage (12.5–25 mg/kg orally every 12 h) was lower in cases vs. controls (OR: 0.08 [0.01–0.71]; P = 0.024). Topical antibacterial drug use was reduced overall; however, only the odds of neomycin use was lower in cases vs. controls (OR: 0.3 [0.1–0.89]; P = 0.029). Cases had higher odds of experiencing improvements in allergic dermatitis categories vs. controls (OR: 7.89 [3.26–19.13]; P < 0.001). Conclusions and clinical importance – Our results suggest that use of oclacitinib to treat allergic dermatitis in dogs is associated with less antibacterial use than other anti-pruritic therapies.